Structural assessment and seismic vulnerability of earthen historic structures. Application of sophisticated numerical and simple analytical models. (1st April 2018) - Karanikoloudis, Georgios; Lourenço, Paulo B.
Highlights: Pushover and dynamic nonlinear analyses produce tensile crack patterns well correlated with the observed ones. From the results of the dynamic identification tests, the system of ties is demonstrated as inactive. Limit analysis can be a sufficient analytical tool in buildings without box behavior. Buttressing, internal and external bracing are proposed, in order to improve structural behavior under seismic loads. The displacement based approach, following the N2 method, was based on two extreme deformed shape vectors. Abstract: Adobe constructions account for a significant portion of the built heritage, associated with early building techniques, material accessibility and low-cost. Nonetheless, adobe buildings, due to their low mechanical properties and overturning resistance, are subject to early structural damage, such as cracking, separation of structural elements and, possibly, collapse in areas of high seismic hazard. The lack of maintenance and absence of adequate retrofitting techniques usually intensifies the loss of historic fabric. The current paper, aims at the structural assessment and seismic safety, in current conditions, of the Church of Kuño Tambo, a religious adobe structure of the 17th century, in Cusco region, in Peru. The inspection and diagnosis involved sonic testing and damage mapping, while ambient vibration tests revealed the modal response of the structure. The assessment of seismic vulnerability, together with the necessity of retrofitting measures were verified through nonlinear static and pushover parametric analyses, complemented with a macro-block limit analysis and a performance based assessment, under local seismic criteria. A more realistic response from dynamically induced ground motions was performed, by a nonlinear time history analysis, according to the Eurocode 8 framework. Through an integrated approach, in situ inspection, testing, numerical and analytical modelling are associated under the scope of reproducing the existing structural damage, the sequence of inelastic behavior and verification of the necessity of retrofitting measures.